Using circuit elements to represent the distributed parameters of a grounding systems under lightning strokes - Seixas, Claudiner Mendes de [UNESP] (2017)
This work presents a proposal to represent electrical grounding systems directly in the time domain. The advantage in using this type of representation is that voltage and current are better understood in this domain and the model can easily be inserted into conventional software such as the Alternative Transient Program (ATP) and Electromagnetic Transient Program (EMTP). The proposed method is applied to horizontal electrodes and vertical rods. The grounding is initially modeled in the frequency domain to obtain harmonic impedance, which is then represented by means of an approximation based on the least squares method directly in the time domain, by passive elements (resistors, inductors and capacitors) associated in series and/or parallel. Validation was achieved by comparing the results with those obtained using the transmission line model and technical literature. The transmission line model (distributed parameters) was used to obtain harmonic impedance of the grounding systems, but any other model could have been used as this process has no effect on the proposed method, making it very versatile and attractive.